The Brimedika Model: Unveiling the Mediating Role of Service Quality Between Green Hospital Aspects and Stakeholder Satisfaction - Januarso, Widodo; Andarini, Sri; Sukoharsono, Eko Ganis; Rachmansyah, Arief (Indonesian Green Technology Journal, 2026)
The rapid growth of Indonesia’s healthcare sector, reflected in the increasing number of hospitals, has also contributed to environmental degradation. The Green Hospital concept is therefore essential to enhance environmental performance in healthcare facilities. However, low awareness of green practices, limited implementation of Green Hospital indicators, and insufficient stakeholder support remain major challenges. Also, the need for this study was due to the intellectual gap relating to the mediation role of service quality to enhance stakeholder satisfaction in a Green Hospital. This study analyzes a service-quality-based Green Hospital model at Brimedika Hospital, Malang, which has demonstrated a strong commitment to environmental initiatives. Using the Slovin formula, 633 respondents were selected from a population of 1,843 individuals. A quantitative approach was applied through questionnaire distribution, and data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results show that environmental, socio-cultural, and economic dimensions significantly influence service quality, which subsequently increases stakeholder satisfaction. Service quality acts as a strong mediator, while the economic aspect also has a direct effect on satisfaction. Strengthening socio-cultural aspects through improved service quality emerges as the most effective strategy for achieving a sustainable Green Hospital model. The study offers novelty by integrating three sustainability dimensions and demonstrating the central role of service quality in enhancing stakeholder satisfaction. The community benefits the most from the model, followed by patients and workers. Strengthened education, community engagement, and eco-friendly facilities are recommended for future development.